Super capacitor electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202611405557.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-16
AI Technical Summary
这种技术偏见的存在,使得常规路径始终围绕如何消除热滞后展开,而非如何利用热滞后,因而难以跳出强度与比表面积此消彼长的困局
本发明超级电容器电极材料在比表面积达到1850m2/g的同时压强还能保持2.5MPa。对比例1中制备的材料比表面积接近1780 m2/g,但压强仅1.2MPa,本发明在相近比表面积下强度提高108%。同时本发明超级电容器电极材料收缩率17%~25%,解决了大厚度产品内外收缩不均导致的性能离散问题。
Smart Images

Figure CN122930740A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of supercapacitor technology, and in particular to a supercapacitor electrode material, its preparation method, and its application. Background Technology
[0002] Supercapacitors, as a novel energy storage device, possess the advantages of high power density and long cycle life, and have broad application prospects in new energy storage, electric vehicles, and portable electronic devices. Electrode materials are the core factor determining the performance of supercapacitors, and carbon aerogels are widely recognized as one of the ideal electrode materials due to their high specific surface area, high porosity, and tunable structure. Currently, carbon aerogels are typically prepared using the sol-gel method, with resorcinol and formaldehyde as precursors, followed by gel aging, solvent replacement, drying, and high-temperature carbonization to obtain the carbon aerogel material. Numerous studies have been reported on this fundamental process, such as improving specific surface area and electrochemical performance by adjusting catalyst dosage, changing drying methods, or introducing activation processes. Some literature has also attempted to introduce fiber reinforcements such as pre-oxidized fibers into resorcinol-formaldehyde (RF) aerogels to improve their mechanical properties, but most of these efforts remain at the level of laboratory thin-layer samples or thermal insulation applications.
[0003] For electrode materials used in supercapacitors, there is a long-standing unresolved contradiction in current technology: high specific surface area and high mechanical strength often come at opposite ends. Pursuing a high specific surface area requires sufficient activation and pore formation, but this significantly weakens the mechanical strength of the carbon framework. Conversely, to meet the strength requirements for electrode fabrication and assembly, some pore structure must be sacrificed, leading to a decline in electrochemical performance. This contradiction can be controlled through precise manipulation in thin-layer samples in the laboratory, but the problem is amplified dramatically when dealing with large-thickness bulk products in industrial production. When the thickness of the carbon aerogel exceeds a certain critical value, the heat transfer delay during carbonization causes the outer layer to reach the decomposition temperature and complete carbonization before the inner layer, while the inner layer's temperature lags behind and the decomposition exothermic peak appears late—the so-called thermal hysteresis effect.
[0004] In existing technologies, this effect is generally considered a process defect during the carbonization of thick products. It can cause asynchronous internal and external shrinkage, residual stress concentration, performance dispersion, and even cracking. Therefore, most studies deliberately avoid the preparation of thick products and focus on thin-layer carbon aerogels with a thickness of less than 2 mm to avoid the adverse effects of thermal hysteresis. Correspondingly, the few patents involving large-size carbon aerogels are mainly aimed at thermal insulation applications. Their performance evaluation indicators focus on low thermal conductivity and pressure, without paying attention to electrochemical performance, and without realizing that the thermal hysteresis effect may have positive regulatory value.
[0005] From a technical perspective, the current technology essentially addresses the challenge of improving the electrochemical performance of thin-layer carbon aerogels in the laboratory. In this scenario, the impact of thermal hysteresis is negligible, and researchers can obtain electrode materials with acceptable performance simply by optimizing the formulation or adjusting the activation conditions. However, when pushing carbon aerogel electrode materials to industrial-grade, thick-film products, the technical problem undergoes a fundamental shift. It is no longer merely about increasing the specific surface area, but about overcoming the internal and external unevenness caused by thermal hysteresis during the thick-film carbonization process, while simultaneously maintaining both mechanical strength and electrochemical performance. Although both types of problems involve carbon aerogels, their process constraints and root causes of contradictions are completely different. More importantly, because the thermal hysteresis effect has long been characterized as a defect, researchers, when facing thick-film products, have conventionally approached either reducing the thickness to eliminate hysteresis or accelerating the heating process to shorten the internal and external temperature difference, without ever considering how to transform this effect into a usable controllable mechanism. This technical bias means that the conventional approach always revolves around how to eliminate thermal hysteresis, rather than how to utilize it, thus making it difficult to escape the dilemma of the trade-off between strength and specific surface area.
[0006] In addition, although activation processes are widely used to increase specific surface area, activation in existing technologies is often independent of the carbonization process and does not take into account the coupling with the microstructure evolution during the carbonization stage. This results in skeleton collapse when activation is over-activated and limited increase in specific surface area when activation is insufficient, making it difficult to achieve synergistic optimization of the two in thick products.
[0007] In summary, existing carbon aerogel electrode material technologies have not yet solved the comprehensive technical problems of positively utilizing the thermal hysteresis effect and synergistically optimizing mechanical enhancement and electrochemical performance in industrial-grade, large-thickness applications. Summary of the Invention
[0008] One objective of this invention is to provide a method for preparing electrode materials for supercapacitors. This method achieves positive utilization of the thermal hysteresis effect by employing a 60-80mm thick pre-oxidized filament / RF organic aerogel, heated and held at an ultra-slow rate of 0.1-0.5℃ / min within a specific temperature range of 400-600℃. This transforms the thermal hysteresis effect, which was originally considered a defect during carbonization, into a means of microstructure control. High specific surface area is then obtained through CO2 activation. Specifically, the reinforced pre-oxidized filament prevents cracking in the thick product during thermal hysteresis → thermal hysteresis control leads to an ordered framework → the ordered framework resists CO2 etching and enables selective pore formation through activation. These three aspects form a positive cycle of crack prevention, ordered structure, and selective pore formation.
[0009] To achieve the above-mentioned objectives, the specific technical solution is as follows: A method for preparing a supercapacitor electrode material includes the following steps: S1. The polyacrylonitrile pre-oxygenated fiber preform is impregnated in a resorcinol-formaldehyde precursor solution, and after gel aging, solvent replacement and drying, a pre-oxygenated fiber / RF organic aerogel with a thickness of 60~80mm is obtained. S2 involves segmented carbonization of the pre-oxidized fiber / RF organic aerogel under an inert atmosphere or vacuum. The segmented carbonization comprises a heating stage, a thermal hysteresis utilization stage, and a high-temperature carbonization stage. Heating section: The temperature is increased from room temperature to 400℃ at a rate of 0.2~1.0℃ / min; Thermal hysteresis utilization section: In the range of 400~600℃, the temperature is increased at a rate of 0.1~0.5℃ / min, and then held for 2~4 hours; High-temperature carbonization stage: Continue heating to 1000~1200℃ for carbonization to obtain carbonized products; S3 activates the carbonized products at 800~1000℃ for 1~4h in a CO2 atmosphere to obtain supercapacitor electrode materials.
[0010] According to embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects: This invention addresses the technical problem of synergistic optimization of mechanical and electrochemical processes for industrial-grade products with a thickness of 60-80mm under thermal hysteresis constraints.
[0011] The heating stage allows the pre-oxidized fiber / RF organic aerogel to complete pre-shrinkage and thermal stabilization, avoiding the accumulation of internal stress at the interface due to the difference in weight loss rates between the pre-oxidized fiber / RF organic aerogel cyclization release of HCN and the RF matrix dehydration condensation release of H2O.
[0012] In the thermal hysteresis utilization section, 400~600℃ is the key temperature range for the breaking of methylene bonds and the rearrangement of carbon atoms (graphitization) in the pre-oxidized filament / RF organic aerogel. Within this temperature range, the methylene bonds and methylene ether bonds of the RF aerogel break, and carbon atoms gain migration energy, thus rearranging between graphene sheets. Ultra-slow heating allows the outer layer to complete the rearrangement and form a rigid shell first. This shell constrains the hysteresis shrinkage of the inner layer, forcing carbon atoms to arrange themselves in an orderly manner. Holding at this temperature for 2~4 hours ensures that there is still sufficient time to complete the rearrangement after the inner layer reaches its hysteresis state.
[0013] The high-temperature carbonization stage further enhances the graphitization degree. This stage no longer relies on the thermal hysteresis effect, so the heating rate can be accelerated to 1~3℃ / min. The activation temperature of 800~1000℃ is selected because the rate constant of the activation reaction C+CO2→2CO changes exponentially with temperature. Below 800℃, the rate is too slow, resulting in a smaller specific surface area; above 1000℃, the rate is too fast, and the ordered microcrystalline region is also etched, reducing the strength. The time window of 1~4h allows the etching depth to penetrate the disordered region without damaging the ordered core, achieving selective pore formation.
[0014] In summary, this invention utilizes the thermal hysteresis effect not by passively enduring the internal and external temperature difference, but by transforming it into a predictable controllable tool through a three-stage carbonization process. There are three prerequisites for its use: First, the thickness must be within the critical window of 60-80 mm. This thickness ensures that the inner layer temperature significantly lags behind when the outer layer reaches 400-600°C, with the hysteresis time matching the holding time of 2-4 hours. If the thickness is less than 60 mm, the hysteresis is insufficient, failing to form the temporal separation of constraint and rearrangement (as in Comparative Example 1); if the thickness is greater than 80 mm, the hysteresis is too large, and the shrinkage stress caused by the temperature difference exceeds the material's strength limit, leading to cracking. Second, the heating rate during the thermal hysteresis utilization stage must be precisely controlled at 0.1-0.5°C / min. This rate ensures that the inner layer is in the ordered rearrangement initiation stage when the outer layer completes its shaping; a heating rate that is too fast will misalign the time window (as in Comparative Example 2), while a heating rate that is too slow will negate the thermal hysteresis effect. Third, the holding time of 2-4 hours ensures sufficient time for the inner layer to complete rearrangement after the hysteresis is reached.
[0015] According to one embodiment of the present invention, if the pre-oxidized filament / RF organic aerogel is heated to the carbonization temperature in one step without setting a thermal hysteresis utilization section at a thickness of 60~80mm, the outer layer and the inner layer will evolve independently and the structural differences will solidify.
[0016] According to one embodiment of the present invention, if one-step carbonization is used instead of segmented carbonization, the temperature rise in the 400~600℃ range is too fast, resulting in the solidification of the difference between the inner and outer layer structures, making it impossible to achieve ordered control.
[0017] According to one embodiment of the present invention, if KOH activation is used instead of CO2 activation, the strong base chemical etching will destroy the ordered framework due to its non-selectivity. + Residues can affect electrochemical stability.
[0018] According to one embodiment of the present invention, the thickness of the pre-oxidized filament / RF organic aerogel is 70~75mm.
[0019] According to one embodiment of the present invention, the preparation method of the pre-oxygenated filament / RF organic aerogel in S1 includes the following steps: S11 dissolves resorcinol and formaldehyde in deionized water at a molar ratio of 1:2, adds sodium carbonate as an alkaline catalyst, adjusts the pH of the solution to 5.0-7.0, and stirs until completely dissolved to obtain the precursor solution; S12 has a fiber density of 0.10~0.20 g / cm³. 3 The polyacrylonitrile pre-oxidized fiber is placed in a mold and pre-compressed to form a polyacrylonitrile pre-oxidized fiber preform with a thickness of 60~80mm. S13 Place the polyacrylonitrile pre-oxidized fiber preform obtained in S12 into the precursor solution obtained in S11. The precursor solution completely immerses the polyacrylonitrile pre-oxidized fiber preform. After evacuating to -20~-98kPa, the pressure is restored to atmospheric pressure. Repeat the evacuation process 2~6 times to ensure that the precursor solution completely immerses and encapsulates the polyacrylonitrile pre-oxidized fiber. S14 is sealed and aged in a constant temperature oven at 50~90℃ for 5~10 days to obtain pre-oxidized filament / RF organic wet gel; S15 involves solvent exchange in anhydrous ethanol with the pre-oxidized filament / RF organic wet gel placed in anhydrous ethanol at a mass ratio of 1:5. The exchange temperature is 40-70℃, and the exchange is performed in 7-10 rounds, with each round lasting 3-5 days. S16 involves drying the solvent-replaced pre-oxygenated filament / RF organic wet gel at a temperature of 40-65℃, a pressure of 10-18MPa, and a time of 3-7 days to obtain a pre-oxygenated filament / RF organic aerogel with a thickness of 60-80mm.
[0020] The pre-oxidized filament / RF organic aerogel obtained by the above preparation method possesses a uniform three-dimensional network structure. This structure forms the basis for the uniform heat transfer along the thickness direction during carbonization, ensuring the spatial controllability of the thermal hysteresis effect. Simultaneously, the uniform distribution of the pre-oxidized filaments in the matrix effectively disperses carbonization shrinkage stress, avoiding localized stress concentration. These two points together provide the structural prerequisite for achieving an ordered gradient structure where the outer layer is first shaped and the inner layer is ordered during the thermal hysteresis utilization section. Furthermore, controlling the molar ratio of resorcinol to sodium carbonate within the range of 50:1 to 500:1, along with pH adjustment from 5.0 to 7.0, maintains the gel reaction rate at an appropriate level, ensuring the uniformity of the network structure. An excessively high catalyst ratio leads to an overly rapid reaction, a coarse and uneven network, and localized loss of control over thermal hysteresis during carbonization; an excessively low ratio results in incomplete reaction, insufficient crosslinking density, and structural collapse during drying. The synergistic control of this ratio range effectively avoids these two extreme cases, ensuring the spatial consistency of the thermal hysteresis effect throughout the entire thickness direction.
[0021] According to one embodiment of the present invention, the drying process in S16 is supercritical carbon dioxide drying.
[0022] Supercritical drying utilizes the properties of CO2 in its supercritical state, which combine gas diffusion and liquid solubility, to remove the solvent from the gel network without a gas-liquid interface, thus preserving the complete three-dimensional network structure. The thick products of this invention require a complete network structure as a physical channel for the uniform transfer of thermal hysteresis effects. Heat conduction from the outside to the inside relies on a continuous solid framework. If the pore structure collapses, causing discontinuity in the framework, the heat conduction path is interrupted, and the temperature difference distribution between the inner and outer layers will deviate from the design window.
[0023] If atmospheric pressure drying is used instead of supercritical drying, the surface tension of the liquid phase during atmospheric pressure drying will cause the pore structure to collapse. In products with a thickness of 60~80mm, the outer layer dries and shrinks first, forming a dense skin that hinders the outward diffusion of the solvent from the inner layer. When the inner layer dries, it is constrained by the skin and generates shrinkage stress, which destroys the uniform heat transfer channels required for the thermal hysteresis effect.
[0024] According to one embodiment of the present invention, in S11, the molar ratio of resorcinol to sodium carbonate catalyst is 50:1 to 500:1.
[0025] The catalyst ratio directly affects the rate of resorcinol-formaldehyde polycondensation and the uniformity of the gel network structure. When there is too much catalyst, the reaction is too fast, the network structure is coarse and uneven, and the thermal hysteresis effect during carbonization is locally out of control, resulting in increased dispersion of shrinkage rate. When there is too little catalyst, the reaction is incomplete, and the insufficient cross-linking density of the network leads to structural collapse during drying.
[0026] According to one embodiment of the present invention, the density of the pre-compressed pre-oxidized filament fiber in S12 is 0.15~0.16 g / cm³. 3 .
[0027] 0.15~0.16g / cm 3 The fiber density and thickness of 70-80mm enable the three-dimensional fiber network to form a reinforcing skeleton that runs through the entire thickness of the product, ensuring that the stress of the outer hard shell and the inner shrinkage during thermal hysteresis is effectively dispersed by the fiber network, thus avoiding macroscopic cracking.
[0028] According to one embodiment of the present invention, the vacuum degree of vacuum impregnation in S13 is -60~-70kPa, and the vacuum is repeatedly pumped for 3 rounds.
[0029] Pre-oxidized fiber bundles consist of thousands of monofilaments, containing a large amount of air. Vacuum impregnation removes this air through repeated vacuum-air-injection cycles, allowing the precursor solution to fully penetrate the fiber bundle and form a uniform RF coating layer on the surface of each monofilament. A vacuum level of -60 to -70 kPa effectively removes air without causing the precursor solution to boil over. Three cycles are sufficient to minimize the residual air inside the fiber bundle.
[0030] If atmospheric pressure impregnation is used instead of vacuum impregnation, the air inside the fiber bundle cannot be removed because atmospheric pressure impregnation cannot remove the air inside the fiber bundle. The solution only coats the outer layer of the fiber bundle and cannot enter the interior, resulting in a large number of pores and defects between the inside of the fiber bundle and the matrix after carbonization, and insufficient interfacial bonding strength.
[0031] According to one embodiment of the present invention, the aging temperature in S14 is 80~90°C and the aging time is 5 days.
[0032] According to one embodiment of the present invention, in S15, solvent replacement involves placing the wet gel in anhydrous ethanol for 7 rounds of replacement, each round lasting 3 days, with a replacement temperature of 45~50°C.
[0033] In this invention, solvent replacement aims to replace water in the wet gel network with ethanol, which has a lower surface tension, thereby reducing capillary forces before supercritical drying. Sufficient solvent replacement ensures the integrity of the organic aerogel's pore structure after supercritical drying. A complete three-dimensional network serves as a structural channel for the uniform transmission of thermal hysteresis during carbonization. If the pore structure collapses locally, the heat conduction path is interrupted, and the thermal hysteresis effect becomes uncontrolled in localized areas, making it impossible to achieve a uniform, ordered gradient.
[0034] According to one embodiment of the present invention, the heating rate of the thermal hysteresis utilization section is 0.2~0.5℃ / min.
[0035] According to one embodiment of the present invention, the heating rate of the high-temperature carbonization section is 1~3℃ / min, and the temperature is maintained for 2~4h after reaching the carbonization temperature.
[0036] The heating rate of 1~3℃ / min ensures that the inner layer temperature can follow the outer layer temperature rise without causing new thermal hysteresis mismatch. The holding time of 2~4 hours allows both the inner and outer layers to achieve sufficient graphitization.
[0037] According to one embodiment of the present invention, in S2, the inert atmosphere is nitrogen or argon.
[0038] According to one embodiment of the present invention, in S3, the CO2 activation temperature is 900°C and the activation time is 2 hours.
[0039] Under these conditions, the difference between CO2 selectively etching disordered regions and preserving ordered regions is greatest, resulting in the most significant selective pore-forming effect.
[0040] The second objective of this invention is to provide a supercapacitor electrode material.
[0041] To achieve the above-mentioned objectives, the specific technical solution is as follows: A supercapacitor electrode material is prepared by the method for preparing supercapacitor electrode materials.
[0042] According to embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects: The electrode material of the supercapacitor of this invention has a specific surface area of 1850 m². 2 While maintaining a pressure of 2.5 MPa, the material prepared in Comparative Example 1 has a specific surface area of approximately 1780 m². 2 / g, but the pressure is only 1.2MPa. The present invention improves the strength by 108% under similar specific surface area. At the same time, the shrinkage rate of the supercapacitor electrode material of the present invention is 17%~25%, which solves the problem of performance dispersion caused by uneven internal and external shrinkage in thick products.
[0043] The specific surface area of carbon aerogel products prepared by existing technologies is only 500-700 m². 2 / g, the pore structure is mainly micropores, lacking the gradient ordering characteristics and carbon fiber reinforcement structure of the product of this invention, and the mechanical strength and electrochemical performance cannot meet the requirements of industrial-grade supercapacitor electrode materials.
[0044] According to one embodiment of the present invention, the specific surface area of the supercapacitor electrode material is ≥1600 m². 2 / g, the specific capacitance at a current density of 1A / g is 312~356F / g, and the 5% deformation pressure is 1.5~2.5MPa.
[0045] According to one embodiment of the present invention, the polyacrylonitrile pre-oxidized fiber is converted into carbon fiber after segmented carbonization, and the carbon fiber is dispersed in the carbonization product to form a three-dimensional carbon fiber network.
[0046] The difference in thermal expansion coefficients between the carbon fiber three-dimensional network and the RF matrix generates pre-compression stress during the carbonization and cooling process. The fiber shrinkage is less than the matrix shrinkage, causing the matrix to be compressed. This pre-compression stress effectively counteracts the weakening effect of activation pore formation on the skeleton, preventing damage to the skeleton caused by activation pore formation.
[0047] A third objective of this invention is to provide applications of the supercapacitor electrode material.
[0048] The specific technical solution is as follows: A supercapacitor includes an electrode sheet and an electrolyte, wherein the electrode sheet comprises the supercapacitor electrode material.
[0049] In addition to the objectives, features and advantages described above, the present invention has other objectives, features and advantages. Attached Figure Description
[0050] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is a flowchart of the preparation method of the supercapacitor electrode material in Example 1. Detailed Implementation
[0051] The terms "preferred," "more preferred," etc., used in this invention refer to embodiments of the invention that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this invention.
[0052] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0053] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of the present invention.
[0054] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in this technical field.
[0055] In the examples and comparative examples, the pre-oxidized fiber preforms were purchased from Hebei Carbon Valley Carbon Fiber Co., Ltd.
[0056] Example 1 A method for preparing a supercapacitor electrode material, the flowchart of which is shown below. Figure 1 As shown, the steps are as follows: S1. Dissolve 12.2 g of resorcinol and 18.0 g of formaldehyde (37 wt% aqueous solution) in deionized water, add 10.2 mL of 0.05 mol / L sodium carbonate solution, adjust the pH to 6.5, and bring the volume to 50 mL to obtain a resorcinol-formaldehyde precursor solution; Pre-oxidized fiber preform (fiber density 0.16 g / cm³) 3 The gel was placed in a stainless steel flat mold, with a 75mm pad to control the thickness, and then placed in an impregnation chamber. The impregnation chamber was placed in a vacuum impregnation system, and a resorcinol-formaldehyde precursor solution was drawn in. The vacuum was then drawn three times to -50kPa. The impregnation chamber was then removed, sealed, and gelled at 90℃ for 5 days. After demolding, the wet gel was removed and immersed in anhydrous ethanol for 7 rounds of replacement, each lasting 3 days, at a replacement temperature of 50℃. The gel was then supercritically dried with CO2 (40℃, 10MPa) for 5 days to obtain a pre-oxygenated filament / RF organic aerogel with a thickness of 75mm. S2 involves segmented carbonization of the pre-oxidized fiber / RF organic aerogel under a nitrogen atmosphere. The segmented carbonization consists of a heating stage, a thermal hysteresis utilization stage, and a high-temperature carbonization stage. Heating section: The temperature is increased from room temperature to 400℃ at a rate of 0.5℃ / min; Thermal hysteresis utilization section: The temperature is increased from 400℃ to 600℃ at a heating rate of 0.2℃ / min, and then held at 600℃ for 3 hours; High-temperature carbonization section: The temperature is increased to 1000℃ at a heating rate of 2℃ / min and carbonized for 3 hours to obtain carbonized products, which are then naturally cooled. S3 activated the carbonized product at 900℃ for 2 hours in a CO2 atmosphere with a gas flow rate of 100 mL / min, and then naturally cooled to obtain the supercapacitor electrode material.
[0057] An electrode sheet is prepared by the following method: The prepared supercapacitor electrode material is cut into the required shape, pressed into shape under 10MPa pressure, and then combined with carbon cloth current collector to assemble into a supercapacitor electrode sheet.
[0058] Example 2 The difference between Example 2 and Example 1 is that the heating rate of the thermal hysteresis utilization section in Example 2 is 0.5℃ / min.
[0059] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the thickness of the pre-oxygenated filament / RF organic aerogel in Comparative Example 1 is 30 mm, and there is no thermal hysteresis utilization section. It is directly heated to 1000 °C at 1 °C / min for carbonization.
[0060] Specifically: A method for preparing a supercapacitor electrode material includes the following steps: S1. Dissolve 12.2 g of resorcinol and 18.0 g of formaldehyde (37 wt% aqueous solution) in deionized water, add 10.2 mL of 0.05 mol / L sodium carbonate solution, adjust the pH to 6.5, and bring the volume to 50 mL to obtain a resorcinol-formaldehyde precursor solution; Pre-oxidized fiber preform (fiber density 0.16 g / cm³) 3 The gel was placed in a stainless steel flat mold, with a 30mm pad to control the thickness, and then placed in an impregnation chamber. The impregnation chamber was placed in a vacuum impregnation system, and a resorcinol-formaldehyde precursor solution was drawn in. The vacuum was then drawn three times to -50kPa. The impregnation chamber was then removed, sealed, and gelled at 90℃ for 5 days. After demolding, the wet gel was removed and immersed in anhydrous ethanol for 7 cycles of replacement, each lasting 3 days, at a replacement temperature of 50℃. The gel was then supercritically dried with CO2 (40℃, 10MPa) for 5 days to obtain a 30mm thick pre-oxygenated filament / RF organic aerogel. S2 performs segmented carbonization of the pre-oxidized fiber / RF organic aerogel under a nitrogen atmosphere. The segmented carbonization consists of a heating stage and a high-temperature carbonization stage. Heating section: The temperature is increased from room temperature to 400℃ at a rate of 0.5℃ / min; High-temperature carbonization section: The temperature is increased from 400℃ to 1000℃ at a heating rate of 1℃ / min for 3 hours to obtain carbonized products, which are then naturally cooled. S3 activated the carbonized product at 900℃ for 2 hours in a CO2 atmosphere with a gas flow rate of 100 mL / min, and then naturally cooled to obtain the supercapacitor electrode material.
[0061] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 has no thermal hysteresis utilization section and directly heats up to 1000°C at 1°C / min for carbonization.
[0062] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 does not undergo CO2 activation.
[0063] Performance testing: The performance of the supercapacitor electrode materials prepared in Examples 1-2 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1. Specific surface area was tested according to GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method"; specific capacitance was tested using the constant current charge-discharge method in a three-electrode system at a current density of 1 A / g; and pressure was tested according to GB / T 8813-2020 "Determination of Compressibility Properties of Rigid Foamed Plastics", with the compressive stress corresponding to 5% deformation as the compressive strength value.
[0064] Table 1 shows the performance test results of the supercapacitor electrode materials prepared in Examples 1-2 and Comparative Examples 1-3.
[0065] As shown in Table 1, both Examples 1 and 2 adopted the thickness range and segmented carbonization process defined by this invention. The only difference was the heating rate of the thermal hysteresis utilization section, which was 0.2℃ / min and 0.5℃ / min, respectively. Comparative Example 1 used a thinner sample with a thickness of 30mm and carbonized at a uniform heating rate of 1.0℃ / min. This invention represents the conventional path in the prior art of circumventing thermal hysteresis by reducing thickness. Comparative Example 2 used a 75mm thickness but also heated at a uniform rate of 1.0℃ / min without a thermal hysteresis utilization section. This scheme was used to verify whether the thermal hysteresis effect itself affects performance and to eliminate the interference of thickness. Comparative Example 3 used a 75mm thickness and included a thermal hysteresis utilization section, but did not perform CO2 activation. This scheme was used to verify the contribution of the activation step.
[0066] Comparative data shows that, although the specific surface area of Comparative Example 1 reaches 1780 m², 2 The surface area of Comparative Example 2 was 1.2 MPa, but the pressure was only 1.2 MPa, indicating that although a high specific surface area could be obtained by simply relying on activation to create pores, the skeleton strength was insufficient and could not meet the mechanical requirements for electrode sheet processing and assembly. Comparative Example 2 had lower performance in all aspects than Comparative Example 1, indicating that in thick products, if the thermal hysteresis effect is not controlled, the residual stress caused by uneven internal and external shrinkage will deteriorate the skeleton structure, resulting in a simultaneous decrease in electrochemical and mechanical properties. Comparative Example 3 had a pressure of 2.8 MPa, but a specific surface area of only 820 m². 2 The specific capacitance is only 125 F / g, indicating that although thermal hysteresis regulation can improve the orderliness and mechanical properties of the framework, without activation and pore formation, the specific surface area and electrochemical performance are seriously insufficient.
[0067] Example 1: Simultaneously at 1850m 2 It achieves excellent levels in both high specific surface area ( / g) and high pressure (2.5MPa). The significance of this combination lies in the fact that, in existing technologies, a similar specific surface area (e.g., 1780m²) is achieved. 2 The product pressure ( / g) is only 1.2 MPa, meaning that the mechanical strength of this invention is approximately doubled under similar specific surface areas. This effect breaks the technical prejudice in the field that activation-based pore formation inevitably weakens the skeleton strength significantly. The key lies in the fact that the pre-constructed ordered skeleton, regulated by thermal hysteresis, improves the carbon skeleton's resistance to CO2 etching, allowing activation to maintain skeleton integrity while fully creating pores. In other words, thermal hysteresis regulation and CO2 activation do not contribute independently, but rather exhibit a clear temporal synergy: first, thermal hysteresis is used to order the skeleton, and then the etching resistance of the ordered skeleton is used to achieve selective pore formation. The existence of this synergistic effect results in a higher specific surface area and higher pressure in Example 1 compared to Comparative Example 2, meaning that two contradictory performance indicators are improved simultaneously. For a 75mm thick product, this dual improvement is achieved under the same process path, further demonstrating that the positive utilization of the thermal hysteresis effect is key to solving the problems of uneven carbonization and performance dispersion in thick products.
[0068] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0069] The above embodiments merely illustrate several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of the present invention should be determined by the appended claims.
[0070] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a supercapacitor electrode material, characterized in that, Includes the following steps: S1. The polyacrylonitrile pre-oxygenated fiber preform is impregnated in a resorcinol-formaldehyde precursor solution, and after gel aging, solvent replacement and drying, a pre-oxygenated fiber / RF organic aerogel with a thickness of 60~80mm is obtained. S2 involves segmented carbonization of the pre-oxidized fiber / RF organic aerogel under an inert atmosphere or vacuum. The segmented carbonization comprises a heating stage, a thermal hysteresis utilization stage, and a high-temperature carbonization stage. Heating section: The temperature is increased from room temperature to 400℃ at a rate of 0.2~1.0℃ / min; Thermal hysteresis utilization section: In the range of 400~600℃, the temperature is increased at a rate of 0.1~0.5℃ / min, and then held for 2~4 hours; High-temperature carbonization stage: Continue heating to 1000~1200℃ for carbonization to obtain carbonized products; S3 activates the carbonized products at 800~1000℃ for 1~4h in a CO2 atmosphere to obtain supercapacitor electrode materials.
2. The method for preparing the supercapacitor electrode material according to claim 1, characterized in that, The preparation method of pre-oxygenated filament / RF organic aerogel in S1 includes the following steps: S11 dissolves resorcinol and formaldehyde in deionized water at a molar ratio of 1:2, adds sodium carbonate as an alkaline catalyst, adjusts the pH of the solution to 5.0-7.0, and stirs until completely dissolved to obtain the precursor solution; S12 has a fiber density of 0.10~0.20 g / cm³. 3 The polyacrylonitrile pre-oxidized fiber is placed in a mold and pre-compressed to form a polyacrylonitrile pre-oxidized fiber preform with a thickness of 60~80mm. S13 Place the polyacrylonitrile pre-oxidized fiber preform obtained in S12 into the precursor solution obtained in S11. The precursor solution completely immerses the polyacrylonitrile pre-oxidized fiber preform. After evacuating to -20~-98kPa, the pressure is restored to atmospheric pressure. Repeat the evacuation process 2~6 times to ensure that the precursor solution completely immerses and encapsulates the polyacrylonitrile pre-oxidized fiber. S14 is sealed and aged in a constant temperature oven at 50~90℃ for 5~10 days to obtain pre-oxidized filament / RF organic wet gel; S15 involves solvent exchange in anhydrous ethanol with the pre-oxidized filament / RF organic wet gel placed in anhydrous ethanol at a mass ratio of 1:
5. The exchange temperature is 40-70℃, and the exchange is performed in 7-10 rounds, with each round lasting 3-5 days. S16 involves drying the solvent-replaced pre-oxygenated filament / RF organic wet gel at a temperature of 40-65℃, a pressure of 10-18MPa, and a time of 3-7 days to obtain a pre-oxygenated filament / RF organic aerogel with a thickness of 60-80mm.
3. The method for preparing the supercapacitor electrode material according to claim 2, characterized in that, In S11, the molar ratio of resorcinol to sodium carbonate catalyst is 50:1 to 500:
1.
4. The method for preparing the supercapacitor electrode material according to claim 2, characterized in that, The vacuum impregnation process in S13 is performed at a vacuum level of -60 to -70 kPa, and the vacuum is repeatedly pumped three times.
5. The method for preparing the supercapacitor electrode material according to claim 2, characterized in that, The aging temperature described in S14 is 80~90℃, and the aging time is 5 days.
6. The method for preparing the supercapacitor electrode material according to claim 2, characterized in that, In S15, solvent replacement involved placing the wet gel in anhydrous ethanol for 7 rounds, with each round lasting 3 days, and the replacement temperature being 45~50℃.
7. The method for preparing the supercapacitor electrode material according to claim 2, characterized in that, The drying process described in S16 is supercritical carbon dioxide drying.
8. The method for preparing the supercapacitor electrode material according to claim 1, characterized in that, The heating rate of the thermal hysteresis utilization section is 0.2~0.5℃ / min.
9. A supercapacitor electrode material, characterized in that, It is prepared by the method for preparing the supercapacitor electrode material according to any one of claims 1-8.
10. A supercapacitor, characterized in that, It includes an electrode sheet and an electrolyte, wherein the electrode sheet comprises the supercapacitor electrode material as described in claim 9.